Bridgeless electrolytic capacitor‐less valley‐fill AC/DC converter for offline Twin‐Bus light‐emitting diode lighting application. Issue 6 (1st July 2013) - Ma, Hongbo; Zheng, Cong; Yu, Wensong; Gu, Bin; Lai, Jih‐Sheng (Jason); Feng, Quanyuan
Abstract : To match the key features of light‐emitting diode (LED) lighting source and further save power, LED lighting driver also requires long life, while maintaining high efficiency, high power factor, pulse‐width modulation dimming and low cost. However, a typical LED lighting driver has the following drawbacks: (i) utilise bulky electrolytic capacitor as storage capacitor with short lifetime; (ii) employ a low‐frequency diode bridge as the rectifier cell; and (iii) engage multiple stages cascade structure for multiple LED strings. To overcome the aforementioned shortages, this study proposed a bridgeless electrolytic capacitor‐less AC/DC converter for offline LED lighting application. In the proposed converter, the conventional diode rectified bridge is replaced by Totem‐pole bridgeless configuration for reducing the number of semiconductors in the line‐current path. Meanwhile, the valley‐fill circuit is introduced to further reduce the capacitor size. As comparison to its counterpart, the proposed circuit requires only one quarter of the capacitor energy when considering the energy amount ( CV 2 ) as the capacitor sizing criterion. Furthermore, the isolation type of the studied circuit is compatible with Twin‐Bus configuration for achieving higher overall system efficiency. Finally, the experimental results, taken from a laboratory prototype rated at 50 W, are presented to verify the effectiveness of the proposed converter.